Respuesta :
Answer:
sum of the first 12 terms of the sequence. 1, -4, -9, -14, . . = -318
Step-by-step explanation:
The given AP is,
1, -4, -9, -14, . . .
first term a = 1,
common difference d = -4 - 1 = -5
number of terms n = 12
Equation:
Sum of n terms of AP, S₁₂ = n/2[2a + (n - 1)d]
S₁₂ = 12/2[(2*1) + (12 - 1)*(-5)]
S₁₂ = 6[2 + (11*(-5))]
S₁₂ = 6[2 - 55] = 6*(-53) = -318
Therefore sum of the first 12 terms of the sequence. 1, -4, -9, -14, . . = -318
Answer:
The sum of first 12 terms of the sequence. 1, -4, -9, -14, . . is -318.
Step-by-step explanation:
Given sequence 1, -4, -9, -14, . . .
We have to find the sum of first 12 terms of the sequence. 1, -4, -9, -14, . .
Consider the given sequence 1, -4, -9, -14, . . .
[tex]a_1=1 ,a_2=-4,a_3=-9[/tex]
First calculate the common difference (d)
[tex]a_2-a_1=-4-1=-5\\a_3-a_2=-9+4=-5[/tex]
Thus, common difference is -5
We know sum of terms in an Arithmetic progression is given by,
[tex]S_n=\frac{n}{2}(2a+(n-1)d)[/tex]
where n is number of terms ,
a = first term
d = common difference
Here, n = 12 , a= 1 , d = -5
[tex]S_{12}=\frac{12}{2}(2(1)+(12-1)(-5))[/tex]
Solving , we get,
[tex]S_{12}=6(2+11(-5))[/tex]
[tex]S_{12}=6(2-55)[/tex]
[tex]S_{12}=6(-53)[/tex]
[tex]S_{12}=-318[/tex]
Thus, the sum of first 12 terms of the sequence. 1, -4, -9, -14, . . is -318.